Use of Supercritical CO2 and R134a as Solvent for Extraction of b-Carotene and a-Tocopherols from Crude Palm Oil: A Review - Hamidah Mohd Setapar, Siti; Khatoon, Asma; Ahmad, Akil; Che Yunus, Mohd-Azizi; Abbas Ahmad Zaini, Muhammad (Asian Journal of Chemistry, 2014)
Supercritical fluid extraction of a-tocopherol and b-carotenoids from crude palm oil offers an excellent method over other existing conventional methods. Supercritical fluid extraction was developed in the early and mid-1980s to reduce the use of harmful organic solvent in the laboratory. The present paper reviews the applications of supercritical fluid extraction technology in extraction of palm oil using CO2 and R 134a fluids. Carbon dioxide is non- toxic, having low critical pressure (74 bar) and temperature (32 °C) which minimize the thermal degradation of product but it has a limited dissolving power for solutes of high polarity and high molecular weight in the supercritical state and it also requires higher pressure of upto 500 bar and this high pressure operation requires high operation cost and high capital cost. R134a is an alternative low pressure, non-reactive, non-flammable, non-toxic, non-ozone depleting and has comparable solvent properties as that of CO2. R-134a needs only its temperature or pressure to be controlled in order to control the conditions of extraction or product isolation. This allows simple control of the process.